True Christianity the doctrine of dispensation in the thought of John William Fletcher (1729-1785) - Frazier, J. Russell (Cambridge : James Clarke, 2014)
John William Fletcher (1729-1785) was a seminal theologian during the early Methodist movement and in the Church of England in the eighteenth century. Best known for the Checks to Antinomianism, he established a theology of history to defend the church against the encroachment of antinomianism as a polemic against hyper-Calvinism. Fletcher believed that the hyper-Calvinist system of divine fiat and finished salvation did not take seriously enough either the activity of God in salvation history or an individual believer's personal progress in salvation. Fletcher made the doctrine of accommodatio.
Front cover; Title page; Copyright; Dedication; Contents; Preface; Acknowledgments; List of Abbreviations; Introduction; 1. The Milieu of Fletcher's Theology; 2. God of nature and of Grace: Theological Foundations for the Doctrine of Dispensations; 3. The Doctrine of Dispensations: An Overview; 4. The Dispensation of the Father; 5. The Dispensation of the Son; 6. The Dispensation of the Spirit; Conclusion; Bibliography; Back cover.
Includes bibliographical references.
Description based on online resource; title from PDF title page (EBSCO, viewed October 7, 2014).
Master record variable field(s) change: 072
Keywords: Fletcher, John, -- 1729-1785.; Fletcher, John, -- 1729-1785.; Methodism -- Doctrines; Dispensationalism; RELIGION / Christianity / Methodist; Dispensationalism; Methodism -- Doctrines; Conduct of life; Fletcher, John, 1729-1785 -- Theology; God (Christianity) -- Attributes; Methodism -- History; Electronic books